Virtual Additive Manufacturing Based on Semicrystalline Polymer Polyetheretherketone (PEEK) - BAJERSKI, Paweł; PECHERSKI, Ryszard Bolesław; CHUDY, Damian (Engineering Transactions, 2019)
Virtual additive manufacturing (AM) is a one of the new directions of research that is necessary to improve AM technology. Abaqus/SIMULIA software allows to simulate the whole process using user subroutines to expand solver capabilities. Two of the most important subroutines are UepActivationVol and UMATHT. The UepActivationVol is related to an activation of elements in accordance with the defined path of the process. The second one the UMATHT is used to implement and combine thermal and crystallization process [2].The presented investigations describe the dual crystallization kinetics model for considered high temperature thermoplastic material Polyetheretherketone (PEEK). Furthermore, it is shown how to analyse the overall process with use of Abaqus/SIMULIA software. The innovation of the presented approach lies in the proper interpreting of the G-Code from Computeraided manufacturing software (CAM), which is an input for the real machines dedicated to AM. The path (coordinates of discrete points) and time of particular steps of the manufacturing process are extracted from the G-Code and are included as input parameters in the simulation code. The discretized part is simplification of the Computer-aided design (CAD) geometry. The final results show the effect implemented in user subroutines. Additionally, Differential Scanning Calorimetry (DSC) test results are presented in order to calculate crystallization and melting parameters.The presented work is the basis of the following investigations covering prediction of residual stresses, volumetric shrinkage and deformations.